Green growth in Mexico, Brazil and Chile: Policy strategies and future prospects - Nicole Grunewald; Inmaculada Martínez-Zarzoso (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2014)
This research focuses on identifying the main policy strategies that could potentially contribute to the advance of three Latin American economies, namely Brazil, Chile and Mexico towards a green growth model that is social and inclusive, given the actual patterns of development of those economies. With this aim, we first identify and describe past and current policies in each country in terms of economic, social and environmental indicators. A detailed analysis follows for Brazil, Chile and Mexico, in which we propose a series of green growth indicators and choose a definition and classification of green growth sectors. We estimate an empirical model to explain the determinants of green house gas emissions and deforestation in Latin American countries. We broadly identify the sectors that contribute to its increase and describe the main green policies applied in each country. In turn we identify the sectors with higher potential for the future. Finally, we present policy recommendations and reflections for the future.
Keywords: 330